2002
DOI: 10.1002/app.11419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of maleated polyolefins as compatibilizers for polyethylene/wood flour composites

Abstract: ABSTRACT:The effects of various types of compatibilizers on the mechanical properties of high-density polyethylene/ wood flour composites were investigated. Functionalized polyolefins, including maleated polyethylenes, polypropylene, and styrene-ethylene/butylene-styrene copolymer, were incorporated to reduce the interfacial tension between the polyethylene matrix and wood filler. Of these, maleated linear lowdensity and high-density polyethylenes gave higher tensile and impact strengths for the composites, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 70 publications
5
64
1
Order By: Relevance
“…For the past decades, research on different types of coupling agents to improve the adhesion between the wood and the plastic has been carried out. The most commonly used coupling agents were maleated polyolefins [16,17]. Felix and Gatenholm found that polypropylene-(maleic anhydride) copolymer was covalently bonded to the fibers through esterification.…”
Section: Introductionmentioning
confidence: 99%
“…For the past decades, research on different types of coupling agents to improve the adhesion between the wood and the plastic has been carried out. The most commonly used coupling agents were maleated polyolefins [16,17]. Felix and Gatenholm found that polypropylene-(maleic anhydride) copolymer was covalently bonded to the fibers through esterification.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers have some significant advantages as reinforcements in polymer composites, such as low cost, low density, biodegradability, availability of renewable natural resources and good mechanical properties [2][3][4][5][6][7]. However, the main disadvantage of these natural fiber=polymer composites seems to be the incompatibility between the hydrophilic natural fibers and the hydrophobic thermoplastic matrix [8][9][10][11][12][13][14]. Thus, in order to develop composites with good properties, it is necessary to improve the interfacial adhesion between the matrix and the cellulosic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for different applications in the industry, rheological and mechanical properties have vital importance in order to classify polymers based on their chemical structures and standardize polymer diversity [6,7]. Researchers analyzed the melt flow index results of foam wood fibers and polypropylene test mixtures.…”
Section: Introductionmentioning
confidence: 99%